Praktik Jual Beli Kupon Doorprize: Perspektif Fiqih Muamalah - Muflikhah, Siti; Ala’uddin, Muhammad; Hasanah, Niswatun (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
In a fun walk event, the distribution of door prizes is the main attraction for participants because it gives them the opportunity to win various attractive prizes through a lottery system. However, this system is entirely dependent on the luck of each participant. This study aims to examine the practice of buying and selling door prize coupons, the views of religious leaders, and analyze them based on the perspective of Fiqh Muamalah. This study is a field research with a qualitative approach. The data sources consist of primary and secondary data, obtained through observation, interviews, and documentation. The results of the study show that the organizing committee provides free coupons as well as paid coupons priced at Rp2,000 per sheet as part of the funding for door prize gifts. This practice was carried out without coordination with religious leaders, indicating a lack of communication with the authorities in religious matters. From the perspective of Fiqh Muamalah, the sale of coupons accompanied by a lottery system is deemed inconsistent with the principles of Islamic commerce and categorized as maisir (gambling), as it involves speculative elements and relies on luck, as emphasized in Surat Al-Maidah verse 90. Keywords: Buying and selling, door prize coupons, Fiqh Muamalah